Gender Differences in Mental Health among Adult Population in Vojvodina, Serbia. - Svetlana Kvrgic; Sanja Harhaji; Vesna Mijatovic Jovanovic; Erzebet Ac Nikolic; Ivana Radic; Sonja Cankovic; Dusan Cankovic (Tehran University of Medical Sciences, 2013)
Mental health and mental disorders are determined by multiple and interacting social, psychological and biological factors which determine the prevalence, onset and course of mental and behavioral disorders. The aim of the study was to evaluate differences in mental health status regarding gender of the adult population in the Province of Vojvodina.Research was carried out as a retrospective cross-sectional study. Data was obtained from the "National Health Survey in Serbia, 2006" database that refers to the representative adult population of Vojvodina, aged 20 and over. A specially designed questionnaire was applied as a research instrument.This study included 3627 examinees, average age 49.9 years. In the month prior to the study, a half of the adult population in Vojvodina (48.4%) was exposed to stress and one third had emotional problems (32.9%), while both stress and emotional problems were more prevalent in females. The average score value on the psychological distress scale (presence of negative conditions and feelings) of all examinees was 64.1 (from 0 to 100) and it was statistically significantly lower in women (62.0), compared to men (66.6) (P